PENGGUNAAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Yosi Elvira; Yania Okestia Ginanda; Victoria Stephanie; Vina Lorenza; Zulfahmi Eka Saputra; Susi Ratna Sari (STKIP Subang, 2026)
This study aims to analyze the use of audio-visual media in social studies learning in elementary schools and to examine its effects and role in improving the quality of learning. The method used is a qualitative library research approach with content analysis techniques. Data were obtained from various scientific literature such as journals, books, and research reports relevant to the topic. The results show that the implementation of audio-visual media in social studies learning is carried out through the use of educational videos that are tailored to the material, learning objectives, and student characteristics. Audio-visual media has been proven to increase students' attention, engagement, motivation, understanding of abstract concepts, and learning outcomes. However, several obstacles were identified, including limited infrastructure, difficulties in selecting appropriate video content, teachers' limited technological skills, and the diversity of student characteristics. In conclusion, audio-visual media plays an important role in improving the quality of social studies learning in elementary schools but requires optimal support to maximize its use.